To Study the Effectiveness of Farm Broadcasts Through Radio in Disseminating Agricultural Information to the Farmers of Trivandrum District - Mothilal Nehru S (Department of Agriculture, College of Agriculture, 1980)
The study was conducted in Trivendrum district of Kerala with the objective of identifying the preference of listeners with reference to mode, programme, duration and frequency of farm broadcasts. It was also decide to study the relationship between selected characteristics of listeners and their mass media exposure behaviour, listening behaviour, communication behaviour, source utilization behaviour and adoption behaviour. The selected charecteristics of the listeners were age, education, occupation, farm size, crops grown, radio ownership and discussion.